2013
DOI: 10.3390/e15093419
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Water Quality Monitoring Points in Sewer Systems using Entropy Theory

Abstract: Abstract:To monitor water quality continuously over the entire sewer network is important for efficient management of the system. However, it is practically impossible to implement continuous water quality monitoring of all junctions of a sewer system due to budget constraints. Therefore, water quality monitoring locations must be selected as those points which are the most representative of the dataset throughout a system. However, the optimal selection of water quality monitoring locations in urban sewer net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Comprehensive reviews can be found in [16][17][18] for different water systems. Entropy theory developed by [19] is used for water quality monitoring networks optimization in rivers [7,20,21], in a bay [22], in sewer systems [23,24] and groundwater [25][26][27]. PCA is used in [8,9] for river water quality monitoring network analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews can be found in [16][17][18] for different water systems. Entropy theory developed by [19] is used for water quality monitoring networks optimization in rivers [7,20,21], in a bay [22], in sewer systems [23,24] and groundwater [25][26][27]. PCA is used in [8,9] for river water quality monitoring network analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Drainage pipe network monitoring is of great significance for urban storm water management. Strengthening pipe network monitoring helps to protect drainage facilities, improve drainage system, and urban information management [1], which is the basis for the construction of information platform. The performance of drainage network is evaluated by on-line monitoring technology to guide the operation management and maintenance design of drainage system.…”
Section: Introductionmentioning
confidence: 99%
“…Memarzadeh, Mahjouri, and Kerachian () proposed a methodology that combines a dynamic FA and discrete entropy theory, which was applied to the River Karoon (Iran). Lee () combined the entropy theory with a genetic algorithm in order to optimize the number of monitoring points in sewer systems. Another integrated technique, which uses a genetic algorithm and geographic information system for the design of effective water quality monitoring network in a large river system was proposed (Park et al, ).…”
Section: Introductionmentioning
confidence: 99%